Effects of dietary L-carnitine and fat type on the performance, milk composition and immunoglobulin in sows, and immunological variables of sows and piglets during late gestation and lactation - Tian, Meili; Wang, Na; Su, Ge; Shi, Baoming; Shan, Anshan (Czech Journal of Animal Science, 2017)
An experiment with a 2 × 2 factorial arrangement of treatments (n = 12 sows/treatment) was conducted to investigate the effect of maternal dietary supplementation with 2 different L-carnitine levels (0 mg/kg and 100 mg/kg) and 2 fat types (3.5% soybean oil and 3.5% fish oil) from day 107 of gestation until weaning (day 21) on performance, milk composition and immunoglobulin, and on the immunological variables of sows and piglets. Blood and milk samples of sows were obtained on days 0 (farrowing), 14, and 21 of lactation. One 21-day-old piglet per litter was selected for the collection of plasma. The average piglet weaning weight and the average daily gain (ADG) were significantly influenced by supplementation with 100 mg/kg of L-carnitine (P < 0.05). Furthermore, fish oil (FO) treatment exhibited an increasing trend in average piglet weaning weight and ADG over soybean oil (SO) treatment (P < 0.1). The concentrations of fat, immunoglobulin G (IgG), and immunoglobulin A (IgA) were increased in colostrums and milk by day 21 by supplementation with 100 mg/kg of L-carnitine (P < 0.05). Supplementation with 100 mg/kg of L-carnitine enhanced the IgG and IgA concentration in the plasma of sows and piglets (P < 0.05). Additionally, the concentrations of IgG and IgA were improved in colostrums by the addition of FO (P < 0.05). The FO treatment also advanced the IgA concentration in the plasma of sows and the IgG concentration in the plasma of piglets (P < 0.05). In conclusion, the addition of 100 mg/kg L-carnitine improved the weight of piglets at weaning, ADG, IgG, and IgA levels in colostrums, and IgG and IgA concentration in the plasma of sows and piglets (P < 0.05). The concentrations of IgG and IgA were significantly increased in colostrums by supplementation with 3.5% FO (P < 0.05). Overall, no significant difference was observed between L-carnitine and FO or SO treatment in immunological variables in this study.
Keywords: fish oil; immunoglobulin; colostrum; performance; sow; soybean oil